Studi Komparasi Self Control Siswa yang Memiliki Kecerdasan Spiritual Tinggi dan Rendah di Kelas XII SMAN I Kota Kediri Tahun Pelajaran 2013/2014 - Mahmudinata, Ady Alfan (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
The study is intended to examine the level of intelligence spiritual studentsof SMAN I Kediri, the self-Control of students having high and low spiritualintelligence, and the different self-control among them. This study used amixed method approach. The data collection was conducted by questionnaire,documentation, interviews and observation. The population of this research isclass XII students of SMAN I Kediri. The results showed that there is a significantdifference between self-control of students who have high spiritual intelligenceand lower in class XII SMAN I Kediri, with the ratio of the average score of132.05: 116.65 15.40 difference. Independent t-test revealed that self-control ofstudents who have high spiritual intelligence is different from the students whohave low spiritual intelligenceof class XII SMAN I Kediri year 2013/2014.